Smart Governance Towards Quality of Life Standards - Nur Afifah; Simson Ginting (International Journal of Business and Quality Research, 2023)
The rapidly growing population that is concentrated in urban areas requires rapid adjustment of government services to achieve a decent standard of living for urban communities. The United Nation projects that around 55% of the world's people live in urban areas. Innovation, creativity and development planning are needed to accommodate people's needs due to the complexity of the city. In this context, Smart City is the answer in dealing with changes in urbanization trends in big cities. The Smart City concept positions the city as an ecosystem of many connected subsystems in supporting the city to remain sustainable (sustainable cities). Smart City is an alternative problem solving to accommodate the need for fast service along with the increasing population density of Medan City which currently reaches 9,283 people/km² in 2022 with a growth rate of 9-10% per year. This study aims to contribute to the lack of empirical studies by analyzing the influence of Smart Governance factors on Quality of Life in the context of Smart City in Medan City, Indonesia. In this study we define five research hypotheses that analyze the effect of Transparency (TRANS) and Collaboration (COL) on quality of life (QL) in Smart City. This research was conducted in the city of Medan using a quantitative correlation approach with SEM (Structural Equation Modeling) analysis techniques operated through the AMOS program. Sampling using nonprobabilistic sampling with random sampling. Based on the results of the analysis, it was found that the variables Transparency (TRANS) and Collaboration (COL) have a positive effect on Quality of Life with a CR value of 3.821 respectively; -3.475; which is greater than ±1.96 and the probability is smaller than 0.05. Thus it can be concluded that the two hypotheses can be accepted